2020
DOI: 10.20944/preprints202012.0675.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nexus Between PI3K/AKT and Estrogen Receptor Signaling in Breast Cancer

Abstract: Signaling from estrogen receptor alpha (ER) and its ligand estradiol (E2) is critical for growth of ~70% of breast cancers. Therefore, several drugs that inhibit ER functions are in clinical use for decades and new classes of anti-estrogens are continuously being developed. Although a significant number of ER+ breast cancers respond to anti-estrogen therapy, ~30% of these breast cancers recur, sometimes even after 20 years of initial diagnosis. Mechanism of resistance to anti-estrogens is one of the intense… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 83 publications
1
11
0
Order By: Relevance
“…135 The ATP-competitive pan-AKT inhibitor ipatasertib (GDC-0068) has shown great promise in the treatment of advanced breast cancer, with capivasertib (AZD5363), uprosertib (GSK2141795), and the allosteric AKT1/2 inhibitor MK-2206 having more limited benefits. 142 Consistent with EGFR and PI3K inhibitors, the most common adverse skin reactions of pan-AKT inhibitors are maculopapular rash (10%-56%) and acneiform eruptions/folliculitis (16%-33%). [143][144][145][146][147][148] AKT1/2 inhibition with MK-2206 has a similar toxicity profile, with reported cases of erythema multiforme.…”
Section: Egfr-pi3k-akt Inhibitorsmentioning
confidence: 99%
“…135 The ATP-competitive pan-AKT inhibitor ipatasertib (GDC-0068) has shown great promise in the treatment of advanced breast cancer, with capivasertib (AZD5363), uprosertib (GSK2141795), and the allosteric AKT1/2 inhibitor MK-2206 having more limited benefits. 142 Consistent with EGFR and PI3K inhibitors, the most common adverse skin reactions of pan-AKT inhibitors are maculopapular rash (10%-56%) and acneiform eruptions/folliculitis (16%-33%). [143][144][145][146][147][148] AKT1/2 inhibition with MK-2206 has a similar toxicity profile, with reported cases of erythema multiforme.…”
Section: Egfr-pi3k-akt Inhibitorsmentioning
confidence: 99%
“…ESR1 gene encodes estrogen receptor 1 that occurs primarily in the medial preoptic area and ventromedial nucleus of hypothalamus, which regulates diverse reproductive functions of both males and females 113 . ESR1 deems to share CTNNB1- 114 and AKT1- 115 mediated signaling pathways to accelerate cancer and neurodegeneration, respectively. Moreover, estrogen inhibits inflammation and immune responses in COVID-19 and reduces the COVID-19 susceptibility in females than in males, because of its higher concentration and greater number of ESR1 receptors in target tissues 116 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that ERα (ESR1) expression is elevated in the lung tissue and myofibroblasts of male patients with IPF, and when ERα antagonists are administered, the decrease in ERα can attenuate the lung fibrosis 55 . The binding of E2 and ERα exists in the cell membrane and nucleus, 56 which can be divided into genomic oestrogen signalling pathways and non‐genomic oestrogen signalling pathways. E2 diffuses through the cell membrane, and when it encounters palmitoylated‐ERα binding on the cell membrane, the ligand (E2) binds to the receptor (ERα), which can activate various cytoplasmic enzymes through non‐genomic interactions, including mediating the PI3K‐Akt pathway to regulate cell proliferation and survival 56–58 .…”
Section: Discussionmentioning
confidence: 99%
“…The binding of E2 and ERα exists in the cell membrane and nucleus, 56 which can be divided into genomic oestrogen signalling pathways and non‐genomic oestrogen signalling pathways. E2 diffuses through the cell membrane, and when it encounters palmitoylated‐ERα binding on the cell membrane, the ligand (E2) binds to the receptor (ERα), which can activate various cytoplasmic enzymes through non‐genomic interactions, including mediating the PI3K‐Akt pathway to regulate cell proliferation and survival 56–58 . In addition, the MAPK/ERK1/2 signal transduction pathway can also be activated to regulate tumour growth and progression 56,59,60 .…”
Section: Discussionmentioning
confidence: 99%